2'-alkynylnucleotides: A sequence- and spin label-flexible strategy for EPR spectroscopy in DNA. - Haugland, M; El-Sagheer, A; Porter, R; Peña, J; Brown, T; Anderson, E; Lovett, J (American Chemical Society, 2016)
Electron paramagnetic resonance (EPR) spectroscopy is a powerful method to elucidate molecular structure through the measurement of distances between conformationally well-defined spin labels. Here we report a sequence-flexible approach to the synthesis of double spin-labeled DNA duplexes, where 2'-alkynylnucleosides are incorporated at terminal and internal positions on complementary strands. Post-DNA synthesis copper-catalyzed azide-alkyne cycloaddition (CuAAC) reactions with a variety of spin labels enable the use of double electron-electron resonance experiments to measure a number of distances on the duplex, affording a high level of detailed structural information.